2016
DOI: 10.14475/kjhpc.2016.19.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Concept Analysis of Nurses’ Acceptance of Patient Deaths

Abstract: Purpose: The purpose of this paper is to identify a theoretical basis of end-of-life care by examining attributes of the concept of the nurses' acceptance of patient deaths. Methods: Walker and Avant's approach to concept analysis was used. A literature study was performed to check the usage of the concept. To identify the attributes of the concept and come up with an operational definition, we analyzed 16 qualitative studies on nurses' experiences of death of patients, published in a national science magazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The type analysis showed different results from those obtained by interviewing the first participant; therefore, interviews continued with nursing professionals who practiced in different clinical environments in various regions. Six themes appeared through a meta-synthesis of systematic literature reviews [ 9 ] on nurses’ experiences of patients’ deaths, as follows: “emotional experiences”, “facilitating good death”, “family support”, “inadequacy of end-of-life care issues”, and “personal and professional growth.” However, these themes did not include characteristics related to a patient’s death such as “attaining through mourning” or “ruminating life and attaining insight of life and death” [ 7 ]. As such, sampling continued for locations, people, and cases to maximize the density of each category based on the properties and dimensions we identified through analyzing qualitative resources.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The type analysis showed different results from those obtained by interviewing the first participant; therefore, interviews continued with nursing professionals who practiced in different clinical environments in various regions. Six themes appeared through a meta-synthesis of systematic literature reviews [ 9 ] on nurses’ experiences of patients’ deaths, as follows: “emotional experiences”, “facilitating good death”, “family support”, “inadequacy of end-of-life care issues”, and “personal and professional growth.” However, these themes did not include characteristics related to a patient’s death such as “attaining through mourning” or “ruminating life and attaining insight of life and death” [ 7 ]. As such, sampling continued for locations, people, and cases to maximize the density of each category based on the properties and dimensions we identified through analyzing qualitative resources.…”
Section: Methodsmentioning
confidence: 99%
“…The results of a concept analysis of nurses’ acceptance of patients’ deaths [ 7 ] showed that nurses’ acceptance could be defined as “the phase which nurses who experienced the death of their patient reach after the grieving process, where they acquire insights about life and death through the reflection of their own lives, and maintain a firm and resolute posture in facing the death of their patients while respecting the dignity of a person in nursing practices.” It has also been reported that nurses’ acceptance of the death of their patients results in holistic end-of-life care and a pursuit of positive living, and these two phenomena are appropriate outcomes that should be sought in end-of-life nursing practices. Therefore, it needs to be understood which causal, contextual, and intermedial conditions interact for nurses to accept patients’ deaths so that they can receive the proper support.…”
Section: Introductionmentioning
confidence: 99%